Anaerobic microbial communities and their potential for bioenergy production in heavily biodegraded petroleum reservoirs. (7th May 2020) - de Rezende, Júlia R.; Oldenburg, Thomas B. P.; Korin, Tetyana; Richardson, William D. L.; Fustic, Milovan; Aitken, Carolyn M.; Bowler, Bernard F. J.; Sherry, Angela; Grigoryan, Alexander; Voordouw, Gerrit; Larter, Stephen R.; Head, Ian M.; et al.
Summary: Most of the oil in low temperature, non‐uplifted reservoirs is biodegraded due to millions of years of microbial activity, including via methanogenesis from crude oil. To evaluate stimulating additional methanogenesis in already heavily biodegraded oil reservoirs, oil sands samples were amended with nutrients and electron acceptors, but oil sands bitumen was the only organic substrate. Methane production was monitored for over 3000 days. Methanogenesis was observed in duplicate microcosms that were unamended, amended with sulfate or that were initially oxic, however methanogenesis was not observed in nitrate‐amended controls. The highest rate of methane production was 0.15 μmol CH4 g −1 oil d −1, orders of magnitude lower than other reports of methanogenesis from lighter crude oils. Methanogenic Archaea and several potential syntrophic bacterial partners were detected following the incubations. GC–MS and FTICR–MS revealed no significant bitumen alteration for any specific compound or compound class, suggesting that the very slow methanogenesis observed was coupled to bitumen biodegradation in an unspecific manner. After 3000 days, methanogenic communities were amended with benzoate resulting in methanogenesis rates that were 110‐fold greater. This suggests that oil‐to‐methane conversion is limited by the recalcitrant nature of oil sands bitumen, not the microbial communities resident in heavy oil reservoirs.